An investigation of phase change induced Marangoni-dominated flow patterns using the Constrained Vapor Bubble data from ISS experiments - Chakrabarti, Unmeelan; Yasin, Ayaaz; Bellur, Kishan; Allen, Jeffrey S. (Frontiers in Space Technologies, 2023)
Kinetic models of liquid-vapor phase change often implicitly assume that the interface is in equilibrium. This equilibrium assumption can be justified for large flat interfaces far from the source of thermal energy, but it breaks down when the liquid surface is near a solid wall, or there is significant interface curvature. The Constrained Vapor Bubble (CVB) experiments conducted on the International Space Station (ISS) provide a unique opportunity to probe this common assumption and also provide unique data and insight into phase change-driven flow physics. The CVB experiment consists of a quartz cuvette partially filled with pentane such that a vapor bubble is formed at the center. The setup is heated and cooled at opposite ends, resulting in simultaneous evaporation and condensation. CVB data from the NASA Physical Science Informatics (PSI) database was used to reconstruct the entire 3D interface shape using interferometric image analysis and obtain an estimate of the net heat input to the bubble. The reconstructed interface shape is used to develop a liquid-only CFD model embedded with a custom-built ``active surface'' method that sets a variable interfacial temperature/phase change flux boundary condition. Phase change flux varies in both the axial and transverse directions, leading to a small (1 K) but discernible temperature variation along the liquid-vapor interface. The positive phase change flux near the heater end (denoting evaporation) gradually reduces and becomes negative near the cooler end (denoting condensation), resulting in an axial bulk flow of liquid from the cold to the hot end. There is also a higher flux in the thin film as opposed to the thick film, resulting in a transverse bulk flow. However, the interfacial temperature gradients along both axial and transverse directions induce a separate thermocapillary flow in a direction opposite to the bulk flows, leading to complex “wavy” flows with recirculation. A qualitative analysis of the flow pattern is presented in this paper and correlated with optical signatures from experimental images.